The expanding family of c-Met inhibitors in solid tumors: a comparative analysis of their pharmacologic and clinical differences. (April 2022) - Fogli, Stefano; Tabbò, Fabrizio; Capuano, Annalisa; Del Re, Marzia; Passiglia, Francesco; Cucchiara, Federico; Scavone, Cristina; Gori, Veronica; Novello, Silvia; Schmidinger, Manuela; Danesi, Romano
Graphical abstract: Highlights: Somatic c-Met mutations and/or amplifications have been observed in several solid tumors, including renal cell carcinoma and lung cancer. Aberrant signaling through c-Met promotes pleiotrophic effects including growth, survival, invasion, migration, angiogenesis and metastasis c-Met inhibitors differ in terms of pharmacodynamic (potency, selectivity) and pharmacokinetic (half-life, exposure) properties that may be clinically relevant. Improved understanding of the clinical pharmacokinetics of c-Met inhibitors can help avoid drug-drug interactions and optimize schedules for continuous in vivo inhibition of c-Met phosphorylation. Abstract: c-Met inhibitors are a class of drugs that include nonselective and selective molecules. These drugs can differ in terms of pharmacodynamic and pharmacokinetic properties that may be clinically relevant. c-Met inhibitors with high potency and selectivity may allow achieving optimal c-Met inhibition in c-Met-driven tumors while reducing unwanted off-target toxicities due to activation of multiple kinases. Nonselective drugs can instead be considered in tumors that also recognize other drivers (e.g., ALK, ROS, VEGF). Improved understanding of the clinical pharmacokinetics of c-Met inhibitors can help avoid drug-drug interactions and optimize schedules for continuous in vivo inhibition of c-Met phosphorylation. The current review article provides a detailed overview of the clinical pharmacology of molecules used in c-Met-driven tumors.